2017
DOI: 10.1016/j.jbiomech.2017.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, histological, and functional properties remain inferior in conservatively treated Achilles tendons in rodents: Long term evaluation

Abstract: Conservative treatment (non-operative) of Achilles tendon ruptures is suggested to produce equivalent capacity for return to function; however, long term results and the role of return to activity (RTA) for this treatment paradigm remain unclear. Therefore, the objective of this study was to evaluate the long term response of conservatively treated Achilles tendons in rodents with varied RTA. Sprague Dawley rats (n=32) received unilateral blunt transection of the Achilles tendon followed by randomization into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…These splints were padded with Webril (Hanna Pharmaceutical; Wilmington, DE), and secured to the skin with silk tape stirrups (3M; St. Paul, MN), and Webril padded CoFlex (Andover Healthcare; Salisbury, MA) straps. This construct was then overwrapped with an additional layer of Webril and CoFlex from the knee to the toes before being coated with poly(methyl‐methacrylate) (PMMA) (Patterson Dental; St. Paul, MN) to resist chewing damage …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These splints were padded with Webril (Hanna Pharmaceutical; Wilmington, DE), and secured to the skin with silk tape stirrups (3M; St. Paul, MN), and Webril padded CoFlex (Andover Healthcare; Salisbury, MA) straps. This construct was then overwrapped with an additional layer of Webril and CoFlex from the knee to the toes before being coated with poly(methyl‐methacrylate) (PMMA) (Patterson Dental; St. Paul, MN) to resist chewing damage …”
Section: Methodsmentioning
confidence: 99%
“…Achilles tendons were harvested at the time of animal sacrifice (n = 6/group), and were processed by standard paraffin procedures and previously described assessments . Cell density and nuclear shape on H&E stained images were independently graded using a scale of one to three for cellularity (1, low; 2, moderate; 3, high) and one to four for nuclei shape (1, spindle shaped; 2, mixed/spindle; 3, mixed/rounded; 4, rounded).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Palmes et al showed in a mice model that the full loading group had reached to non-injured levels of mechanical properties after 16 weeks, whereas the immobilized group had not (43). This effect could not be seen in a rat model (21). However, an immobilized group was not evaluated in this study so the full loading tendons might still be better compared to immobilization.…”
Section: Comparison With Other Studiesmentioning
confidence: 61%
“…The improvement by mechanical loading is usually evaluated in the early phases of Achilles tendon healing, 1-3 weeks after injury (3,9,16,18,22,27), but later evaluation has also been made (21,43). Most animal studies evaluating the effect of full loading during the early phase of Achilles tendon healing have shown beneficial effects (3,9,16,18,19,22).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%